Research based design for informal assessment techniques - Bohsali, Layal Adel (Beirut Lebanese American University. School of Arts and Sciences. Education Department, 2010)
The purpose of the present study is to provide support for teachers to assess grade two students using informal assessment techniques. This project explores the importance of informal assessment techniques and their effects on both the students and the teachers. Then, this project provides teachers with guidelines on how to implement some of the assessment techniques that are compatible to the Lebanese Curriculum.
: Mémoire
Keywords: Evaluation Scolaire; School Evaluation